2018
DOI: 10.1177/1077699018754909
|View full text |Cite
|
Sign up to set email alerts
|

News Borrowing Revisited: A 50-Year Perspective

Abstract: Analyzing 50 years’ of New York Times international news coverage ( N = 20,765), this study extends research on the “shrinking international news hole,” levels of press freedom, agent (e.g., Times correspondent), and “borrowed” news—information gleaned from local media, including social media. Data show a recent, growing role for social media and an increase in news borrowing, while foreign coverage declined; slight resurgence in foreign coverage during the last quarter-century; reduced wire copy use but incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The phenomena of interest may be either manifest or latent . Manifest content refers to concrete concepts that are clearly present or absent, whereas latent content refers to more abstract concepts that cannot be measured directly but instead are identified by several indicators (Riffe et al., 2018). For instance, if a goal is to hand‐label the presence or absence of water in typically dry streambeds based on high‐quality webcam images, “water” is a relatively manifest phenomenon, and thus the codebook would require minimal information about how to identify it.…”
Section: How Qca Can Address Limitations and Problems Of Training Sup...mentioning
confidence: 99%
“…The phenomena of interest may be either manifest or latent . Manifest content refers to concrete concepts that are clearly present or absent, whereas latent content refers to more abstract concepts that cannot be measured directly but instead are identified by several indicators (Riffe et al., 2018). For instance, if a goal is to hand‐label the presence or absence of water in typically dry streambeds based on high‐quality webcam images, “water” is a relatively manifest phenomenon, and thus the codebook would require minimal information about how to identify it.…”
Section: How Qca Can Address Limitations and Problems Of Training Sup...mentioning
confidence: 99%
“…A follow-up study by Caliendo et al (1999) found only a moderate correlation between the severity of physical abuse and volume of news coverage by the New York Times . While there is evidence that human rights coverage increased in the 1990s (Barnhurst, 2016; Ramos et al, 2007; Riffe et al, 2018), media attention tended to concentrate on a few nations that already commanded public attention from the Northern media (Thrall et al, 2014; Wu, 2000). ‘The media magnify the presence of certain human rights problems whilst minimizing the relevance of others’, observe Tumber and Waisbord (2017: 3) in their encyclopedic handbook on media and human rights.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…The main reason for the newspapers to do this is because they identify specific articles as a matter of interest for their own readerships (cf. Riffe et al, 2018; also see e.g. replies from the editors regarding why they borrow news arctiles from other news sources).…”
Section: Data Setmentioning
confidence: 99%
“…replies from the editors regarding why they choose to focus on these specific topics; cf. Riffe et al, 2018), which in turn reflects the ideological stance of the newspaper itself (Islentyeva, 2019;Jonsson, 2014;Maydell, 2010). The recognition of readership is also evident in the selection of news articles under the theme of travel.…”
Section: Research Questionmentioning
confidence: 99%